Organic Selenium Ameliorates Staphylococcus aureus-Induced Mastitis in Rats by Inhibiting the Activation of NF-κB and MAPK Signaling Pathways - Liu, Kangjun; Ding, Tao; Fang, Li; Cui, Luying; Li, Jun; Meng, Xia; Zhu, Guoqiang; Qian, Chen; Wang, Heng; Li, Jianji (Frontiers in Veterinary Science, 2020)
Mastitis is an economically important disease in dairy cows, which is often caused by Staphylococcus aureus (S. aureus). Selenium is an indispensable element for physiological function and contributes to reduce injury of the mammary glands in mastitis. However, adequate sources of selenium have always been an important consideration for livestock. Therefore, the study aimed to explore the protective effect and mechanism of Selenohomolanthionine (SeHLan) on mastitis induced by S. aureus. The S. aureus-induced rat model was established and three doses (0.2, 2, 20 μg/kg body weight/day) of dietary OS were supplemented. The bacterial load, histopathology, and myeloperoxidase (MPO) of the mammary glands were performed and determined. Cytokines, including interleukin (IL)-1β, TNF-α, and IL-6, were detected using qRT-PCR. The key proteins of NF-κB and MAPK signaling pathways were analyzed by Western blot. The results revealed that OS supplementation could reduce the recruitment of neutrophils and macrophages in mammary tissues, but did not decrease S. aureus load in the tissues. The overexpression levels of IL-1β, TNF-α, and IL-6 induced by S. aureus were inhibited after OS treatment. Furthermore, the increased phosphorylation of NF-κB and MAPKs proteins were also suppressed. The results suggest that dietary supplementation with adequate OS during pregnancy contributes to protect the mammary glands from injury caused by S. aureus and alleviate the inflammatory response.